About the (in)competence of the European institutions to reform the public systems of national pensions in the light of the EU law and the international treaties - Sánchez-Rodas Navarro, Cristina (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
In Spain, after the worldwide economic and financial crisis of 2008, important legislative reforms have been carried out in order to control the public deficit and therefore will be able to comply not only with the provisions emanating from the European Union Law but also with the International Treaties ratified by our country. Due to their amount, contributory old-age pensions are the most important item in the General State Budget. There is a widespread belief that the restrictive reforms on Spanish pensions that have been enacted in recent years were inevitable because they were imposed by provisions emanating from the European Union and /or international treaties. The purpose of this article is, on the one hand, to demonstrate that the competence to legislate on Social Security matters is, and continues to be, the exclusive competence of the State. And, on the other hand, to verify how the last reforms in the field of pensions obey to national legislative initiatives, in no way imposed by European Law or international Law.